On‐Chip Quantum Optics with Quantum Dot Microcavities. (9th October 2012) - Stock, E.; Albert, F.; Hopfmann, C.; Lermer, M.; Schneider, C.; Höfling, S.; Forchel, A.; Kamp, M.; Reitzenstein, S.
<x xml:space="preserve">Abstract</x> A novel concept for on‐chip quantum optics using an internal electrically pumped microlaser is presented. The microlaser resonantly excites a quantum dot microcavity system operating in the weak coupling regime of cavity quantum electrodynamics. This work presents the first on‐chip application of quantum dot microlasers, and also opens up new avenues for the integration of individual microcavity structures into larger photonic networks. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>